Cultural and estivation resources and their role inincreasing the volume of tourism movement In Lattakia Governorate - ناصر, لميس (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The civilizational record of Lattakia Governorate, in the western region of Syria, in all successive historical periods left on mankind, traces of ancient and spread throughout the province, giving it a distinct historical dimension with cultural elements such as castles, museums and ancient cities, attracting tourism lovers from different parts of the world .Lattakia governorate also embraces at the same time a set of estivation resources such as nature reserves, and summer resorts such as the slunfeh resort and kassab resort, and due to the presence of a functional role for cultural and summer resources crystallized through the positive impact of them in the local economy, by increasing the number of hotel guests and tourist nights in Lattakiagovernorate. Through this research we focus on the study of the geographic distribution of cultural and estivation resources in Lattakia governorate, as well as the study the tourism movement, finally, to the study of number of hotel guests and tourist nights, and the prospects for it developmentCultural and estivation resources in Lattakia governorate, we have reached that the tourists directed to estivation areas more than archcological and curtural areas by 34%, and the numbers of hotel Syrian guests have incrcased by 95 % compared with the arab guests during the crists.